Carotid Endarterectomy Versus Carotid Artery Stenting With Double-Layer Micromesh Stent in Carotid Angioplasty: Network Meta-Analysis - Evelyn Natalie Hailianto; Fransiska Livia; Jesselyne Aurelia Santoso Kho; Clayton Christopher Hermawan; Jason Michael Prawira; Julius July (Universitas Pelita Harapan, 2025)
Introduction: Carotid endarterectomy (CEA) remains the gold standard for carotid stenosis, but modern carotid artery stenting (CAS) with double-layer micromesh stents (e.g., CGuard, Roadsaver [RS]) offers potential reductions in peri-procedural embolic risk. However, comparative evidence between CEA and modern CAS remains limited. Methods: A systematic search of PubMed, ScienceDirect, and Europe PMC (June 23,2025) identified randomized and observational studies on symptomatic or high grade asymptomatic carotid stenosis using terms including “double-layer stent,” “micromesh,” “Roadsaver,” “CGuard,” and “carotid endarterectomy.” Reviews, meta analyses, and case reports were excluded. Comparisons included single-layer CAS vs. CEA, single-layer CAS vs. CGuard/RS, and indirect CEA vs. CGuard/RS. Outcomes were neurological complications and neurological death. Study quality was assessed using Cochrane RoB 2.0 and Newcastle-Ottawa Scale (NOS). A frequentist random effects network meta-analysis was performed using MetaInsight. Results: Eleven studies (7 RCTs, 4 observational; n=9483) were included. Seven had moderate RoB 2.0 risk, while three observational studies had fair quality and one study had good quality according to NOS. No significant difference was detected in neurological complications between CEA and CGuard/RS (OR 0.79; 95% CI 0.34-1.80), and neurological death was similar among CEA, CGuard/RS, and CAS. When compared with conventional CAS, CEA (OR 0.90; 95% CI 0.69–1.18) and CGuard/RS (OR 1.04; 95% CI 0.30–3.65) showed no significant differences. The direct comparison between CEA and CGuard/RS also demonstrated no significant effect (OR 0.86; 95% CI 0.24–3.11).Conclusions: This study found no significant differences in stroke prevention or safety CEA and DLMS. Larger comparative studies are required to establish their relative clinical effectiveness.Keywords: carotid artery stenting; carotid endarterectomy; micromesh stent; single layer stent; stroke